EFEKTIVITAS PENGGUNAAN APLIKASI SRIKANDI DALAM PENGELOLAAN ARSIP DI DINAS PERHUBUNGAN KABUPATEN OGAN KOMERING ULU SELATAN PROVINSI SUMATERA SELATAN - Liansah, Defry; Yahnu Wiguno Sanyoto; Eva Susanti (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine the effectiveness of using the SRIKANDI application in archive management at the Dinas Perhubungan Ogan Komering Ulu Selatan (OKU Selatan) Regency Sumatera Selatan Province. The study employs a qualitative method using primary and secondary data obtained through observation, interviews, and documentation. Seven informants participated in the study, selected using a purposive sampling technique. The data analysis process includes several stages: information collection through interviews, data reduction, data presentation, and conclusion drawing. The findings show that the use of the SRIKANDI application in archive management at Dinas Perhubungan OKU Selatan Regency is effective. The implementation of the application improves efficiency and supports better management of archives. Further development and additional training are still required for staff who have not fully mastered the operation of the SRIKANDI application to optimize its use in archive management.